Content Analyses of Scientific Articles from All Issues Published in Sport Mont Journal in 2009 - Katarina Dragutunovic (Journal of Anthropology of Sport and Physical Education)
Sport Mont Journal is a print and electronic scientific journal aims to present easy access to the scientific knowledge for sport-conscious individuals using contemporary methods. As one of the most prestigious scientific journals in Montenegro, is published three times a year. The aim of this paper was to classify the articles published in the 2009 journal, by scientific disciplines. On that occasion, we used the method of content analysis. During this period, 95 titles were published, which are classified according to the fields of sports science - biomechanics, physiology, sports medicine, anthropology, methodology, methodology, pedagogy, sociopsychology, anthropomotorics, anthropometry, research in sports and others. It has been found that the most numerous scientific research papers in sport and socio-psychology of sports (30), sport anthropology (25) and sports techniques (13). They show us that in this period a lot of attention was devoted to research in sport and sociopsychology of sports, where personalities, attitudes and characteristics were examined as important determinants of success in sports. In addition to these, there were still many scientific papers from other fields, which cover from social, humanistic and natural sciences. The integration of papers in all areas of sports science is not a simple task, even if we consider this one of the most prestigious journals in this region, the quality of the work itself is crucial.